EVALUASI KERASIONALAN PENGGUNAAN OBAT DENGAN STANDAR PELAYANAN MEDIS SEBAGAI PENGENDALI PADA BEBERAPA PENYAKIT PASIEN RAWAT JALAN DI RSUD PANEMBAHAN SENOPATI BANTUL - , Rahyanti Fitriah ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: To achieve satisfactory medical services, good prescription is important. Good prescription requires diagnostic accuracy and appropriateness in medicine choice. To ensure the quality of therapy, standard treatment guideline essential towards rational use of medicine. Thus, evaluation on rational use of medicine should be carried to focus on quality of therapy. Aim: To analyze the appropriateness of medicine use with standard treatment as guideline for Low back pain, Pulmonary Tuberculosis, Urinary Tract Infections in outpatient department in Panembahan Senopati Regency Hospital, Bantul. Methods: Descriptive case study design was applied, using qualitative and quantitative data. Qualitative data were obtained by in-depth interview while quantitative data were gathered from document observation. Data collected by conducting in-depth interviews for qualitative data, and for quantitative data were gathered from documents observation. Results: On LBP, average number of drugs per prescription was 2.66 items, percentage of generic drugs was 74.3%, percentage of antimicrobial was 1.7%, percentage of injection was 72.7%, percentage of hospital formulary was 88.2%, percentage of DOEN was 18.5%, percentage of therapeutic guideline was 71%, percentage of psychotropic drugs was 12.7%, percentage of systemic steroid was 6,3%. While Pulmonary TB, average number of drugs per prescription was 3.15 items, percentage of generic drugs 56.4%, percentage of antimicrobial was 100%, percentage of injection was 0%, percentage of hospital formulary was 100%, percentage of DOEN was 71.9%, percentage of therapeutic guideline was 71.8%, percentage of psychotropic drugs was 0%, percentage of systemic steroid was 0%. For UTI, average number of drugs per prescription was 1.75 items, percentage of generic drugs 69.5%, percentage of antimicrobial was 92%, percentage of injection was 0%, percentage of hospital formulary was 94.3%, percentage of DOEN was 33.4%, percentage of therapeutic guideline was 54.8%, percentage of psychotropic drugs was 1.3%, percentage of systemic steroid was 1.3%. Conclusion : Pattern of drug prescription in Panembahan Senopati regency hospital, Bantul with medical standard service as guideline for Low Back Pain, Pulmonary Tuberculosis, Urinary Tract Infections was not yet rational. Usage of medical service standard as controlling instrument and the quality of medical service standard itself should be periodically improved.